Functional single-nucleotide polymorphism (rs762551) in CYP1A2 gene affects white coffee intake in healthy 20- to 40-year-old adults - Nikrandt, Grzegorz; Mikolajczyk-Stecyna, Joanna; Mlodzik-Czyzewska, Monika; Chmurzynska, Agata (Nutrition research (New York, N.Y.), 2022)
Coffee is one of the most consumed beverages in the world, but the extent to which it is consumed is affected by both environmental and genetic factors. Genome-wide association studies and candidate date association studies have identified several gene variants associated with increased consumption of coffee. Functional single-nucleotide polymorphisms in rs762551 (cytochrome P450 1A2 [CYP1A2]) and rs5751876 (adenosine receptor A2A [ADORA2A]) has been linked to individual caffeine response. Coffee intake has been shown to affect lipid metabolism. We thus hypothesize that rs762551 (CYP1A2) A allele carriers consume more coffee than C allele carriers and that rs5751876 (ADORA2A) C allele carriers consume less coffee than T allele carriers. Additionally, we hypothesize that CYP1A2 genotype can modulate serum glucose concentrations and lipid profile. A total of 421 participants aged 20 to 40 years were recruited from 2016 to 2018 in Poznań, Poland. Genotyping of CYP1A2 and ADORA2A was performed using TaqMan probes. Individuals with AA CYP1A2 genotype consumed relatively more coffee with milk (72.81 ± 10.15 mL/1000 kcal vs 43.38 ± 6.42 mL/1000 kcal, P = .008) and with milk or cream than did C allele carriers, whereas the rs5751876 ADORA2A polymorphism was not associated with coffee or tea intake. Additionally, subjects with AA CYP1A2 genotype had 10% higher serum triacylglycerol (TG) concentrations than C allele carriers. This study suggests that CYP1A2 rs762551 polymorphism is associated with coffee intake and serum TG concentrations in healthy 20- to 40-year-old adults. Coffee intake is associated with both genetic and environmental factors. We tested whether CYP1A2 rs762551 (A>C) polymorphism is associated with coffee intake and whether it can modulate serum glucose concentrations and lipid profile. People with AA genotype, namely fast caffeine metabolizers, drink more coffee with milk and white coffee and have lower levels of triacylglycerol than C-allele carriers (slow metabolizers). [Display omitted]